If both x minus 2 and x minus one upon two are the factors of px2 + 6x + r, then show that p equals to r.
Answers
Answered by
0
hey mate
in its given (x-1)and (x-2) are factors of equation px^2+6x+r
so when x-2 is factor
x=2 is a solution fr the quadratic eq
when we substitute we will get
4p+12+r=0 (eq1)
similarly when we substitute x=1p+6+r=0 (eq2)
now solve both equation
eq1-eq2
u will get :3p+6=0
so p=-2
now substitute value of p in eq 2
u will get r as -4
i hope this helps u!!
in its given (x-1)and (x-2) are factors of equation px^2+6x+r
so when x-2 is factor
x=2 is a solution fr the quadratic eq
when we substitute we will get
4p+12+r=0 (eq1)
similarly when we substitute x=1p+6+r=0 (eq2)
now solve both equation
eq1-eq2
u will get :3p+6=0
so p=-2
now substitute value of p in eq 2
u will get r as -4
i hope this helps u!!
vaibhav35632:
okk
Similar questions
Geography,
8 months ago
CBSE BOARD X,
8 months ago
Math,
8 months ago
Sociology,
1 year ago
Math,
1 year ago